Effect of Natural Catalysts in Fast Pyrolysis of Cassava Rhizome in a Free - Fall Reactor - ปัตติยะ อดิศักดิ์ (Srinakharinwirot University Engineering Journal, 2018)
Fast pyrolysis of cassava rhizome was carried out in a free-fall reactor to investigate the effect of pyrolysis temperature and natural catalysts on the pyrolysis products. The pyrolysis temperatures of 350, 400 and 500°C were tested for non-catalytic experiments in order to determine optimum temperature for maximising the bio-oil mass and energy yields. The results showed that the maximum bio-oil mass yield of 62wt% with the corresponding energy yield of 46% was achieved at 400°C. The non-catalytic bio-oils produced had a higher heating value (HHV) of 15.8 MJ/kg. Other properties of the non-catalytic bio-oil such as pH, viscosity and density were found to meet the standard requirements of the ASTM D7544-12. The pyrolysis temperature of 400°C was selected for the catalytic pyrolysis experiments applying a constant catalyst temperature of 500°C. Activated natural zeolite, perlite and kaolin catalysts were tested in the biomass catalytic pyrolysis experiments. Although all catalysts led to bio-oil mass and energy yield reduction, certain bio-oil properties could be improved. Among the catalysts studied, kaolin was found to be the most suitable catalyst. The use of kaolin gave the bio-oil mass yield of 46 wt% and energy yield of 20%. In addition, the HHV of the kaolin-catalysed bio-oil could be increased to 19.5 MJ/kg.